PENGEMBANGAN USAHA UMKM LOKAL TERHADAP PENGELOLAAN KEUANGAN MELALUI KONSEP AKUNTANSI - Septianah, Reza; Aprilani, Triana Lidona; Fathurrahman, Fathurrahman; Utamie , Dara Nida (Jurnal Kompetitif : Media Informasi Ekonomi Pembangunan, Manajemen dan Akuntansi, 2025)
This study aims to analyze the "development of local micro, small, and medium enterprises (MSMEs) infinancial management through accounting concepts in Narmada District, West Lombok" by applying effectivefinancial management based on accounting principles. MSMEs play an important role in the local economy, yetthey often face challenges in financial management that can hinder their growth. The research method used isa qualitative approach, with in-depth interviews with MSME owners, and data collection techniques includingdocumentation, literature study, and interviews. The results of the study show that the application of basicaccounting principles can improve transparency and accountability in MSME financial management.Additionally, training and mentoring in financial management have proven to be effective in encouragingbusiness growth. This research is expected to contribute to the development of MSMEs in the region and serveas a reference for stakeholders involved in improving the financial management capacity of local MSMEs.